Almost orthogonal subsets of vector spaces over finite fields. (June 2022) - Mohammadi, Ali; Petridis, Giorgis
Abstract: We prove various results on the size and structure of subsets of vector spaces over finite fields which, in some sense, have too many mutually orthogonal pairs of vectors. In particular, we obtain sharp finite field variants of a theorem of Rosenfeld and an almost version of a theorem of Berlekamp.